Authentication of Geographical Origin and Crop System of Grape Juices by Phenolic Compounds and Antioxidant Activity Using Chemometrics. Issue 3 (10th February 2015) - Granato, Daniel; Koot, Alex; Schnitzler, Egon; van Ruth, Saskia M.
Abstract The main goal of this work was to propose an authentication model based on the phenolic composition and antioxidant and metal chelating capacities of purple grape juices produced in Brazil and Europe in order to assess their typicality. For this purpose, organic, conventional, and biodynamic grape juices produced in Brazil (n = 65) and in Europe (n = 31) were analyzed and different multivariate class‐modeling and classification statistical techniques were employed to differentiate juices based on the geographical origin and crop system. Overall, Brazilian juices, regardless of the crop system adopted, presented higher contents of total phenolic compounds and flavonoids, total monomeric anthocyanins, proanthocyanidins, flavonols, flavanols, cyanidin‐3‐glucoside, delphinidin‐3‐glucoside, and malvidin‐3, 5‐glucoside. No differences were observed for trans‐resveratrol, malvidin‐3‐glucoside, and pelargonidin‐3‐glucoside between countries and among crop systems. A total of 91% of Brazilian and 97% of European juices were adroitly classified using partial least squares discriminant analysis when the producing region was considered (92% efficiency), in which the free‐radical scavenging activity toward 2, 2‐diphenyl‐1‐picrylhydrazyl, content of total phenolic compounds, gallic acid, and malvidin‐3‐glucoside were the variables responsible for the classification. Intraregional models based on soft independent modeling of class analogy were able to differentiate organic from conventional Brazilian juices as well as conventional and organic/biodynamic European juices.